BVOC responses to realistic nitrogen fertilization and ozone exposure in silver birch. (June 2016) - Carriero, G.; Brunetti, C.; Fares, S.; Hayes, F.; Hoshika, Y.; Mills, G.; Tattini, M.; Paoletti, E.
Abstract: Emission of BVOC (Biogenic Volatile Organic Compounds) from plant leaves in response to ozone exposure (O3 ) and nitrogen (N) fertilization is poorly understood. For the first time, BVOC emissions were explored in a forest tree species (silver birch, Betula pendula ) exposed for two years to realistic levels of O3 (35, 48 and 69 ppb as daylight average) and N (10, 30 and 70 kg ha −1 yr −1, applied weekly to the soil as ammonium nitrate). The main BVOCs emitted were: α-pinene, β-pinene, limonene, ocimene, (E)-4, 8-dimethyl-1, 3, 7-nonatriene (DMNT) and hexanal. Ozone exposure increased BVOC emission and reduced total leaf area. The effect on emission was stronger when a short-term O3 metric (concentrations at the time of sampling) rather than a long-term one (AOT40) was used. The effect of O3 on total leaf area was not able to compensate for the stimulation of emission, so that responses to O3 at leaf and whole-plant level were similar. Nitrogen fertilization increased total leaf area, decreased α-pinene and β-pinene emission, and increased ocimene, hexanal and DMNT emission. The increase of leaf area changed the significance of the emission response to N fertilization for most compounds. Nitrogen fertilization mitigated the effects of O3 exposure on total leaf area, while the combined effects of O3 exposure and N fertilization on BVOC emission were additive and not synergistic. In conclusion, O3 exposure and N fertilization have the potential to affect global BVOC via direct effects on plant emission rates and changes in leaf area. Graphical abstract: Highlights: Ozone exposure stimulated BVOC emission. Responses to an episodic O3 metric were stronger than to a seasonal one. N fertilization showed compound-specific effects (from inhibition to stimulation). N-driven changes in total leaf area affected the magnitude of these effects. O3 and N impacted BVOC emission individually, with no significant interactions. Abstract : Ozone exposure increased BVOC emission and reduced total leaf area, while N fertilization increased total leaf area and showed compound-specific effects (from inhibition to stimulation) on BVOC emission.